Clinical outcomes with ventricular pacing or dual-chamber pacing for sinus-node dysfunction: a nationwide matched control study. (24th May 2021) - Fauchier, L; Bodin, A; Bisson, A; Herbert, J; Ah-Fat, V; Spiesser, P; Pierre, B; Clementy, N; Babuty, D
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction.Evidence from randomized trials suggests that, in patients with sinus-node dysfunction (SND), physiologic pacing (dual-chamber, DDD) may be superior to single-chamber (ventricular, VVI) pacing because it is associated with lower risks of atrial fibrillation and stroke, better exercise capacity and lower risk of pacemaker syndrome. However, benefits on mortality and risk of heart failure have not been demonstrated and these issues have not been fully evaluated in large "real life" analyses. Objective.The aim of our study was to assess and compare clinical outcomes within the first 30 days and during a longer-term follow-up with the two types of pacing at a nationwide level for patients with SND. Methods and results.Using the administrative hospital database in France 2010-2020, 52, 974 patients with SND were included in the analysis: 4, 069 patients had VVI pacing and 48, 905 had DDD pacing. Patients with leadless VVI pacemakers were excluded of the analysis. After propensity score matching 2, 213 patients with VVI pacemaker were matched 1:1 with 2, 213 patients treated with DDD pacemaker. In the matched analysis, patients with DDD pacemakers had a lower rate of all-cause (hazard ratio HR 0.711, 95%CI 0.61-0.828) and cardiovascular death (HR 0.628, 95%CI 0.48-0.818) within the 30 days after implantation. There were no significant differences for incidence of tamponade (HR 0.666, 95%CI 0.11-3.992), pneumothorax (HR 1.000, 95%CI 0.32-3.105), hemothorax (HR 0.800, 95%CI 0.21-2.982), major bleeding (HR 0.824, 95%CI 0.68-1.005) and transfusion (HR 1.016, 95%CI 0.83-1.243). During subsequent follow-up (mean: 3.0 ± 2.8 years), risk of all-cause death in the matched population was significantly lower in the DDD group than in the VVI pacemaker group (HR 0.683, 95%CI 0.60-0.784). Patients with SND treated DDD pacemakers also had a lower risk of cardiovascular death (HR 0.569, 95%CI 0.44-0.732), new-onset atrial fibrillation (HR 0.638, 95%CI 0.58-0.706), ischemic stroke (HR 0.685, 95%CI 0.53-0.887) and hospitalization for heart failure (HR 0.758, 95%CI 0.68-0.850) than those treated VVI pacemakers, whilst risk of endocarditis was not significantly different (HR 0.986, 95%CI 0.50-1.951).  Conclusion.Patients with SND treated with DDD pacemakers had better clinical outcomes compared to those treated with VVI pacemakers. DDD pacing was associated with lower risks of death, cardiovascular death, new-onset atrial fibrillation, ischemic stroke, hospitalization for heart failure. DDD pacing was neither associated with a higher risk of complication on the short-term nor of endocarditis on the longer-term.